PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT BTN TBK CABANG BEKASI - Hotman Napitupulu (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
The purpose of this study was to analyze the effect of organizational culture and work environment on the performance of employees of PT Bank Tabungan Negara (Persero) Tbk. The population of this study are employees PT Bank Tabungan Negara (Persero) Tbk. The research results show a positive and significant influence of organizational culture and work environment on employee performance PT Bank Tabungan Negara (Persero) Tbk.